Order-preserving transformations with restricted range: regularity, Green’s relations, and ideals - Worachead Sommanee (2018)
© 2015, Springer Basel. Let X be a chain and OT(X) the full order-preserving transformation semigroup on X. Let Y be a fixed nonempty subset of X and let OT(X, Y) be the subsemigroup of OT(X) of all order-preserving transformations with ranges contained in Y. In this paper, we investigate the order-preserving transformation semigroupOF(X,Y)={α∈OT(X,Y):Xα=Yα}.Here, we characterize when an element of OF(X, Y) is regular and describe Green’s relations in OF(X, Y). Moreover, we give a simpler description of Green’s relations, characterize the ideals of OF(X, Y) when Y is a finite subset of X, and apply these results to prove that OF(X, Y) is idempotent generated.